Towards a Knowledge Building Community: From Guided to Self-Organized Inquiry - Stefano Cacciamani (The Canadian Network for Innovation in Education (CNIE), 2010)
Over four academic years a design experiment was conducted involving four online university courses with the goal of shifting from Guided to Self-Organized Inquiry to foster Knowledge Building communities in the classroom. Quantitative analyses focused on notes contributed to collective knowledge spaces, as well as reading and building-on notes of others. All team members, including teachers, contributed at high levels. Students tended to produce more notes in the guided-inquiry approach but read more and demonstrated more even distribution of work as part of self-organized inquiry. Qualitative data focused on strategies students reported as new to their school experience. Strategies fell into three categories common to both guided and self-organizing inquiry: elaborating course content for depth of understanding, collaboration in an online environment, and metacognition, with greater reflection on idea development. Distinctive aspects of self-organized inquiry, according to student reports, included going beyond given information, linking new understandings and personal experiences, attention to the collective works of the community, and learning from instructor's strategies.